2021
DOI: 10.1088/1742-6596/1764/1/012099
|View full text |Cite
|
Sign up to set email alerts
|

Application of Web Based Learning to Measure Students Learning Interest

Abstract: The advancement of information and communication technology requires teachers to create various innovative learning media based on information technology; one of those media is database learning. Database is a course which uses to discuss the framework in developing the application programs. Hence, the technology needs to be intensified in improving skills in the field of software engineering and as a source of learning for students in secondary schools. This research is designed to develop web based learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Similarly, Hapsari & Zulherman (2021) found that animated video learning media, supported by the Canva platform, effectively motivated students and improved learning outcomes. The effectiveness of web-based learning in enhancing self-regulated learning abilities was further confirmed by Ferdiansyah & Irfan (2021) and Sulyanah et al (2021). Based on these findings, the researchers of this study employed a website-based learning media, utilizing the Canva platform.…”
Section: Introductionmentioning
confidence: 61%
“…Similarly, Hapsari & Zulherman (2021) found that animated video learning media, supported by the Canva platform, effectively motivated students and improved learning outcomes. The effectiveness of web-based learning in enhancing self-regulated learning abilities was further confirmed by Ferdiansyah & Irfan (2021) and Sulyanah et al (2021). Based on these findings, the researchers of this study employed a website-based learning media, utilizing the Canva platform.…”
Section: Introductionmentioning
confidence: 61%
“…Several studies investigated the impact of Web-based instruction on students' learning as compared to face-to-face instruction. Sulyanah, Hasanah & Untari (2021) conducted a study to measure learners' interest using web-based learning. The results showed that web based learning media is declared very feasible with a percentage of 82.6%.…”
Section: Web-based Learning In Efl Educationmentioning
confidence: 99%
“…In English teaching, interest-oriented teaching method refers to how to make students have a strong need for English, stimulate their interest, and thus generate great internal drive [3][4][5][6][7]. Stimulating students' interest in learning is to make students have the enthusiasm to learn English, which usually comes from both needs and interests [8][9][10][11][12][13][14]. Personalized recommendation technology, which is widely used in Internet platform, can also be applied to the field of higher education, so as to achieve accurate matching between learning resources and college students, meet students' personalized learning preference needs, reduce students' learning resource selection cost, and provide students with more diversified and rational learning resource supply [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%